Multidimensional Service Quality Evaluation in a Private English Course Institution: A SERVQUAL-Adapted Percentage-Based Performance Mapping - Yayah Takziyah; Sumangala Sumangala (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to evaluate multidimensional service quality in a private English course institution based on students’ perceptions using an adapted SERVQUAL framework and percentage-based categorical classification to determine institutional performance levels across key academic, administrative, infrastructural, financial, and certification dimensions Methodology: This study employed a quantitative descriptive survey design using a structured SERVQUAL-adapted questionnaire with a five-point Likert scale. Data were collected from active students through total sampling. Instrument reliability was tested using Cronbach’s Alpha. Data were analyzed using descriptive statistical techniques and percentage-based performance categorization. Main Findings: The results indicate that overall service quality is categorized as good to very good across all ten dimensions. The highest scores were found in certification credibility, small-class system effectiveness, consultation facilities, and scheduling flexibility, while replacement class availability received the lowest score but remained within the good category. Novelty/Originality of this study: This study introduces a multidimensional percentage-based performance mapping model that adapts SERVQUAL specifically to private English course institutions. Unlike prior studies focusing on general satisfaction indices, this research integrates academic, administrative, infrastructural, financial, and certification dimensions into a unified categorical benchmarking framework.